Activated carbon adsorbent for adsorbing methylbenzene and preparation method of activated carbon adsorbent

By preparing and modifying super activated carbon, the problem of degradation of activated carbon adsorption performance under high humidity conditions is solved, and efficient adsorption of low-concentration toluene and good cycle stability are achieved.

CN119869459AInactive Publication Date: 2025-04-25INT CENT FOR BAMBOO & RATTAN

Patent Information

Application Number
CN202510287079.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-12
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Under high humidity conditions, the adsorption performance of activated carbon is reduced, especially in low-concentration VOCs environments, the adsorption capacity of the adsorbent is poor, making it difficult to effectively treat toluene in the indoor air.

Method used

Super activated carbon was prepared by carbonizing and activation of lignin, and fluorocarbon source was covalently grafted on its surface through organic [2+1] cycloaddition reaction to form hydrophobically modified super activated carbon LSAC-3-CF2.

Benefits of technology

Under high humidity conditions, LSAC-3-CF2 significantly improves the adsorption capacity to low concentrations of toluene, maintains high adsorption capacity, and has excellent cycling stability and thermal regeneration performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869459A_ABST
    Figure CN119869459A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of activated carbon preparation, in particular to an activated carbon adsorbent for adsorbing methylbenzene and a preparation method thereof.The preparation method comprises the steps that 1, lignin is carbonized, heated to the target temperature according to the constant heating rate and naturally cooled to the room temperature, and lignin carbon is obtained; step 2, mixing and grinding the lignin carbon and an activating agent, heating to a target temperature according to a constant heating rate, naturally cooling to room temperature, taking out, and washing the surface to be neutral by using a hydrochloric acid solution and deionized water in sequence to obtain lignin-based super active carbon; and step 3, modifying the lignin-based super active carbon, namely mixing and heating the lignin-based super active carbon, a fluorine carbon source, an initiator and methylbenzene, and cooling to obtain the modified lignin-based super active carbon.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of activated carbon preparation, and in particular to an activated carbon adsorbent for adsorbing toluene and a preparation method thereof. Background Art

[0002] With changes in lifestyles and production patterns, people now spend over 90% of their time indoors, and the continued deterioration of indoor air quality has a significant impact on human health and comfort. Nearly 99% of the global population breathes air that does not meet standards. Toluene, a common organic solvent in building and interior decoration materials, poses a health hazard to humans even with long-term exposure at low concentrations. Therefore, the treatment of trace toluene has become an important research topic. Among various treatment methods, adsorption has attracted widespread attention due to its low cost, high efficiency, and ease of operation.

[0003] Although metal-organic frameworks (MOFs) and their derived porous carbons, zeolite molecular sieves, and silica gel have been used to capture VOCs, their high cost and complex processes limit their industrial applications. In contrast, activated carbon (AC) has become an ideal material for indoor air purification due to its diverse raw material sources, large surface area, and excellent adsorption performance. However, under high humidity conditions (≥50RH%), the adsorption performance of activated carbon still faces challenges. Indoor air usually contains a large amount of water vapor, and water molecules compete with toluene molecules for adsorption. Water molecules preferentially occupy adsorption sites, reducing the adsorption capacity for VOCs. In addition, the concentration of VOCs in indoor air is usually low, and as the concentration decreases, their ability to replace water molecules on the adsorbent surface weakens. Therefore, when dealing with low-concentration VOCs, the adsorbent exhibits poor adsorption capacity.

[0004] Therefore, providing an activated carbon that still has high adsorption capacity for low-concentration VOCs under high humidity conditions has become an urgent problem to be solved. Summary of the Invention

[0005] In order to solve the above problems, the present invention provides an activated carbon adsorbent for adsorbing toluene and a preparation method thereof, comprising the following steps:

[0006] Step 1: carbonizing lignin by heating it to a target temperature at a constant heating rate and then naturally cooling it to room temperature to obtain lignin charcoal;

[0007] Step 2: The lignin charcoal and the activator are mixed and ground in a ball mill, and then heated to the target temperature at a constant heating rate. After naturally cooling to room temperature, the charcoal is taken out and the surface is washed to neutrality with hydrochloric acid solution and deionized water to obtain lignin-based super activated carbon.

[0008] Preferably, before carbonizing the lignin, the lignin is purified. The purification operation is as follows: mixing lignin with water in a mass ratio of 1:20, stirring, filtering, heating in a water bath, adjusting the pH to 2 with a 2M hydrochloric acid solution, stirring, centrifuging, removing the supernatant, and drying the precipitate to obtain purified lignin.

[0009] Preferably, the lignin-based super activated carbon is modified, and the modification operation is to mix the lignin-based super activated carbon, a fluorocarbon source, an initiator and toluene, heat them, and then cool them to obtain the modified lignin-based super activated carbon.

[0010] Preferably, the ratio of the lignin-based super activated carbon, the fluorocarbon source, the initiator and the toluene is 15 mg:30 mg:3 mg:1 mL.

[0011] Preferably, the fluorocarbon source is TMSCF2Br, the initiator is n-Bu4NBr, and heating is performed under a nitrogen atmosphere at a heating temperature of 110°C for 2 hours.

[0012] Preferably, in step 1, heating is performed under a nitrogen atmosphere with a nitrogen flow rate of 200 mL / min, the constant heating rate is 3° C. / min, the target temperature is 500° C., and the target temperature is maintained for 2 h.

[0013] Preferably, the mass ratio of the lignin charcoal to the activator in step 2 is 1:(1-4).

[0014] Preferably, in step 2, the activator is KOH, the grinding speed is 500 rpm, the grinding time is 2 min, heating is carried out under a nitrogen atmosphere, the flow rate is 200 mL / min, the constant heating rate is 5°C / min, the target temperature is 850°C, and the target temperature is maintained for 1 h.

[0015] The present invention has the following advantages:

[0016] (1) The hydrophobic modification method of the present invention is simple to operate, has mild conditions, and is low in cost, and can achieve the super-hydrophobic property (water contact angle of 153.7°) of super activated carbon.

[0017] (2) The hydrophobic modification method of the present invention retains the adsorption sites of super activated carbon to the greatest extent. Compared with the reported literature, its total specific surface area and micropore specific surface area only decreased by 4.9% and 8.8%.

[0018] (3) The hydrophobic super activated carbon prepared in this invention exhibits ultra-high adsorption capacity for low-concentration toluene under high humidity conditions. At 50% and 80% relative humidity, the saturated adsorption capacity of LSAC-3-CF2 for 1 ppm toluene was 145.9 mg / g and 46.0 mg / g, respectively.

[0019] (4) The hydrophobic modification method of the present invention covalently grafts trace amounts of hydrophobic groups -CF2 onto the surface of activated carbon via an organic [2+1] cycloaddition reaction. Compared to previously reported physical modification methods, the activated carbon of the present invention exhibits excellent cyclic stability. Even after three cycles, it maintains a high adsorption capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are merely embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying any creative work.

[0021] Figure 1 (a) N2 adsorption–desorption isotherm, (b) QSDFT pore size distribution (the inset shows the magnified pore area), (c) XRD pattern, (d) Raman spectrum, (e) FT-IR spectrum, and (f) TG–DTG curve of unmodified LSAC.

[0022] Figure 2 SEM-EDS mapping images of (a, b) LSAC-3 and (d, e) LSAC-3-CF2, and water contact angles of (c) LSAC-3 and (f) LSAC-3-CF2.

[0023] Figure 3 (a) N2 adsorption-desorption isotherm, (b) QSDFT pore size distribution (the inset shows the magnified pore size distribution), (c) measured spectrum (the inset shows the F1s region), high-resolution XPS (d) C1s, (e) F1s, (g) Si2p and (h) O1s spectra, (f) IR spectrum and difference spectrum of LSAC-3 and LSAC-3-CF2.

[0024] Figure 4 Toluene adsorption isotherms of LSAC-3 and LSAC-3-CF2 at (a) 298 K and (b) 318 K, respectively. (c) Sips model fitting and (d) DSLF model fitting of LSAC-3 and LSAC-3-CF2 at 298 K.

[0025] Figure 5 Toluene breakthrough curves (a, b) and t10% (c) of LSAC-3 and LSAC-3-CF2 adsorbing 1 ppm toluene under different humidity conditions (0, 50, 80, and 90 RH%) at 298 K, PFO adsorption rate constants k1 (d) and PFO fitting kinetic curves (e, f) of LSAC-3 and LSAC-3-CF2.

[0026] Figure 6 Toluene breakthrough curves of (a) LSAC-3 at 50 RH% and (b) LSAC-3-CF2 at 80 RH% for 1 ppm toluene adsorption at different temperatures (298, 318, and 338 K), and cyclic performance of (c) LSAC-3 and (d) LSAC-3-CF2 for 1 ppm toluene adsorption at 80 RH%, respectively.

[0027] Figure 7 (a) Breakthrough curve of trace toluene at 298 K under dry conditions, and (b) the corresponding breakthrough time and adsorption capacity of LSAC when Ct / C0 = 0.05.

[0028] Figure 8 The 10% toluene adsorption capacity (C t / C0=0.1), (a)S micro / S BET (b) S meso ;(c)V meso ; (d) S BET ;(e)V t ; (f) V micro ;(g)S micro ;(h)V meso and S meso / S BET ofall LSACs.

[0029] Figure 9 SEM-EDS mapping images and the corresponding atomic ratios of (ac) LSAC-1, (df) LSAC-2, and (gi) LSAC-4.

[0030] Figure 10 (a) XRD pattern, (b) Raman spectrum, and (c) TG-DTG curve of LSAC-3-CF2.

[0031] Figure 11 SEM-EDS spectra of LSAC-3 and LSAC-3-CF2.

[0032] Figure 12 Water vapor adsorption isotherms of LSAC-3 and LSAC-3-CF2 at 298K.

[0033] Figure 13 The q of LSAC-3 and LSAC-3-CF2 to 1 ppm toluene under different humidity conditions (0, 50, 80 and 90 RH%) at 298 K is shown in Table 1. e 90%.

[0034] Figure 14YN and Thomas fitting models for the toluene adsorption breakthrough curves of LSAC-3 and LSAC-3-CF2 at 298K under different humidity conditions (0, 50, 80 and 90RH%).

[0035] Figure 15 The concentrations of toluene desorbed from LSAC-3 (a) and LSAC-3-CF2 (b) using dry nitrogen at different temperatures. DETAILED DESCRIPTION

[0036] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without making any creative efforts shall fall within the scope of protection of the present invention.

[0037] Example 1

[0038] This embodiment provides a method for preparing an activated carbon adsorbent for adsorbing toluene, comprising the following steps:

[0039] Purification of lignin:

[0040] 100g of lignin was dissolved in an excess of deionized water (mass ratio 1:20). The solution was filtered through a metal sieve to remove insoluble solid impurities and magnetically stirred for 30 minutes to completely dissolve it, yielding an alkaline lignin solution (initial pH = 12). The solution was then heated in a 70°C water bath, and a 2M hydrochloric acid solution was added dropwise to the filtrate to adjust the pH to 2. The solution was magnetically stirred for another 2 hours. After the reaction, the filtrate was centrifuged at 4000 rpm for 20 minutes to separate the solid and liquid phases. The solid precipitate was washed several times with deionized water until neutral. Finally, the solid precipitate was dried in an oven at 60°C to yield purified lignin.

[0041] Step 1: Place the purified lignin in a tubular furnace for carbonization at a heating rate of 3°C / min, heat to 500°C under a nitrogen atmosphere, maintain for 2 h, and obtain lignin charcoal (LC).

[0042] In step 2, LC and KOH were mixed and milled in a ball mill at 500 rpm for 2 minutes. The mixture was then activated in a tube furnace at a heating rate of 5°C / min. The mixture was heated to 850°C under a nitrogen atmosphere and held for 1 hour at a nitrogen flow rate of 200 mL / min to obtain LSAC-X, where X is the mass ratio of KOH to LC, and X can be 1, 2, 3, or 4, respectively. Finally, the LSAC-X sample was washed with 1M hydrochloric acid solution and deionized water until neutral, then dried in an oven at 103°C for later use.

[0043] In step 3, 30 mg of LSAC-3 substrate, 60 mg of TMSCF2Br fluorocarbon source, 6 mg of n-Bu4NBr initiator, and 2 mL of toluene were added sequentially to a dry press tube. The mixture was heated at 110°C under a nitrogen atmosphere for 2 hours and then cooled naturally to room temperature. The modified sample was collected and washed several times with anhydrous ethanol and deionized water. Finally, the filtered solid was dried in an oven at 60°C and reserved for future use. This was designated LSAC-3-CF2.

[0044] Test Example 1

[0045] Samples before and after modification, namely LSAC-1, LSAC-2, LSAC-3, LSAC-4 and LSAC-3-CF2, were taken and characterized by BET, XRD, Raman spectroscopy, FTIR, TG, SEM-EDS, water contact angle, water vapor adsorption isotherm and XPS.

[0046] Static adsorption test: The adsorption isotherms of toluene on different samples were measured at 298 K and 318 K using a vacuum vapor adsorption instrument. Before the test, 30 mg of the sample was degassed at 573 K for 12 h. The adsorption isotherms were fitted using the Sips model and the DSLF model. The Sips model and the DSLF model are described as Equations (1) and (2), respectively:

[0047]

[0048] Where q1 is the adsorption amount per unit mass of adsorbent (mg / g), Q1 is the maximum adsorption amount of gas on the adsorbent surface (mg / g), K1 is the adsorption equilibrium constant, which represents the adsorption affinity between molecules, P is the absolute pressure of the gas (kPa), P0 is the saturation pressure of the gas (kPa), and n1 is the adsorption index, which is used to describe the heterogeneous adsorption characteristic index in the adsorption process.

[0049]

[0050] Where q2 is the adsorption amount per unit mass of adsorbent (mg / g), Q2 and Q3 are the maximum adsorption amounts of gas at site A and site B, respectively (mg / g), K2 and K3 are the adsorption equilibrium constants at site A and site B, respectively, P is the absolute pressure of the gas (kPa), P0 is the saturation pressure of the gas (kPa), and n2 and n3 are used to describe the heterogeneous adsorption characteristic indices of site A and site B, respectively.

[0051] Isostatic heat of adsorption (Q ad ) is used to evaluate the interaction between the adsorbate molecules and the adsorbent and is calculated by using the Clausius–Clapeyron equation (Eq. (3)) at different temperatures and pressures:

[0052]

[0053] Where Q ad is the isosteric heat of adsorption (kJ / mol), R is the gas constant (8.314×10 -3 kJ / (mol·K)), T1 and T2 are the adsorption temperatures (K), and P1 and P2 are the absolute pressures (kPa) at the corresponding temperatures.

[0054] The free energy change (ΔG0) associated with the adsorption process is calculated by formula (4):

[0055] ΔG0=RTln(P / P0) (4)

[0056] Where ΔG0 (kJ / mol) is the change in Gibbs free energy.

[0057] Dynamic adsorption tests were performed on samples before and after modification (LSAC-1, LSAC-2, LSAC-3, and LSAC-4). N₂ was used as the carrier gas for the adsorption tests, and 20 ppm toluene standard gas diluted with N₂ served as the toluene source gas. The gas flow path consisted of three gas streams: dry gas, wet gas, and toluene. The gas flow rates were controlled by mass flow meters. The gas streams were mixed in a gas collection flask and passed through a fixed-bed quartz tube (6 mm inner diameter, 350 mm length) containing the sample (25 mg). The reaction temperature was 25°C. The total flow rate of the mixed gas stream was controlled by a mass flow meter at 200 mL / min. The initial inlet concentration of toluene was 1 ppm, and the target humidity levels were 0, 50, 80, and 90 RH%. Prior to the test, the samples were heated to 120°C and maintained at this temperature for 2 hours under an N₂ atmosphere (200 mL / min) to remove surface moisture and impurities. The initial inlet and outlet concentrations of toluene were detected by GC, and the equilibrium adsorption capacity of toluene was calculated by formula (5):

[0058]

[0059] Where q e is the toluene adsorption capacity (mg / g), C0 and C t are the initial inlet concentration of toluene and the outlet concentration of toluene at time t (mg / L), m is the mass of the adsorbent (g), t is the time (min), and V is the gas flow rate (L / min).

[0060] To further evaluate the effect of moisture on the samples, the breakthrough curves and dynamic adsorption behaviors of LSAC-3 and LSAC-3-CF2 at different humidity levels were fitted and calculated using the Yoon and Nelson (YN) model and the Thomas model. The YN equation and the Thomas equation are expressed as Equations (6) and (7), respectively:

[0061]

[0062] Where C0 and C t are the inlet and outlet concentrations of toluene (mg / L), K YN is the rate constant of the YN model (h-1), t is the adsorption time (h), τ is the time required to break through 50% of the adsorbate (h), K T is the rate constant of the Thomas model (L / (h·mg)), q e is the equilibrium adsorption capacity (mg / g), and F is the gas flow rate (L / h).

[0063] In addition, among the kinetic models, the pseudo-first-order (Eq. (8)) and pseudo-second-order (Eq. (9)) models are widely used to determine the adsorption type.

[0064] ln(q e -q t )=ln q e -k1t(8)

[0065]

[0066] Where q t is the adsorption capacity at time t (mg / g), t is the adsorption time (h), q e is the equilibrium adsorption capacity (mg / g), k1 and k2 are the pseudo-first-order and pseudo-second-order adsorption rate constants (h-1), respectively.

[0067] The pore structure of pristine LSACs was measured by N2 adsorption-desorption isotherms at 77 K ( Figure 1 a). Pore size distribution (PSD) curve is as follows Figure 1 b, and the related structural parameters are shown in Table 1. All N2 isotherms show typical type I behavior according to the IUPAC classification, reflecting that all LSACs are characterized by micropores (S micro / S BETFor LSAC-1 and LSAC-4, the obvious H4-type hysteresis loop at P / P0>0.4 indicates that the sample surface has heterogeneous characteristics, which is related to the existence of multiple functional adsorption sites, including micropores and mesopores, while LSAC-2 and LSAC-3 have no obvious hysteresis loop, showing relatively uniform micropore adsorption sites. The above phenomenon can be seen in Figure 1 In addition, with the increase of KOH dosage, the SBET of LSACs increases, especially the SBET of LSAC-3 and LSAC-4 are 2535m 2 / g and 3224m 2 / g. In conclusion, LSACs with high microporosity were successfully prepared using KOH as a pore activator.

[0068] Subsequently, the basic crystal structure, graphitization degree, surface functional groups and thermal stability of the prepared LSACs were fully characterized. XRD results showed that the crystal structures of all LSACs had no significant differences. They all had two broad peaks at about 2θ = 22° and 43°, corresponding to the (002) and (100) planes of graphitic carbon, respectively. Figure 1 c). From the low intensity and broad peak of (002), it can be inferred that LSACs mainly contain amorphous carbon. Raman spectroscopy shows that LSACs have two broad peaks corresponding to the D band (~1344 cm -1 ) and G belt (~1590cm -1 ), representing sp 2 In-plane vibration of hybridized carbon atoms and vibration of carbon atoms caused by defects or disordered structures ( Figure 1 d) I D / I G The value quantitatively reflects the graphitization degree and defect content of carbon materials. D / I G The values ​​imply that the graphitization degree of LSACs is not affected by the KOH dosage (Table 4), which can also be confirmed by the XRD results.

[0069] FTIR spectra showed that all LSACs had a -1 、808cm -1 and 1093cm -1 There are three obvious peaks ( Figure 1 e). 1580cm -1 The absorption band at 808 cm is attributed to the C=O group, which is due to the high content of oxygen-containing functional groups in lignin. -1 and 1093cm -1 The absorption bands are attributed to the symmetric and asymmetric Si-O-Si stretching vibrations, respectively.

[0070] Combined with the XRF results (Table 3), SiO2 was confirmed to be the main Si species in the original LSAC-3 (relative content of 96.5 wt%). These observations explain why LSAC-3 has excellent adsorption capacity for trace amounts of toluene at relatively high humidity even without any hydrophobic modification. Figure 1 The TGA and DTG curves in (f) show that the mass of all LSACs remains almost unchanged below 500°C, indicating that LSACs have good thermal stability. The TGA and DTG curves of all LSACs are similar, indicating that the increase in KOH dosage has little effect on the thermal stability of LSACs.

[0071] Subsequently, the breakthrough curve of LSACs was tested with trace toluene (1 ppm), and the 5% breakthrough time (t5%) and adsorption capacity (q e 5%), and select the LSAC with the best trace toluene adsorption performance for further surface hydrophobic modification. Figure 7 As shown, t5% and q of LSACs e 5% first increases and then decreases with the increase of KOH feed amount. In particular, LSAC-3 shows the highest adsorption performance, with t5% of 2112min and q e 5% is 62.88 mg / g. In addition, the linear fitting between adsorption capacity and pore structure parameters was applied to explore the potential relationship to explain its excellent trace toluene adsorption performance. According to Table 1 and Figure 8 , q of 10% adsorption capacity on LSACs e With S micro / S BET Positive correlation (R 2 =0.891), and S meso (R 2 =0.743) and S meso / S BET (R 2 These results further prove that higher microporosity is more suitable for the adsorption of trace toluene.

[0072] The morphology and element distribution of LSACs are shown in Figure 2. Figure 2 、 Figure 9 and Figure 11 As shown. It is worth noting that, except for LSAC-4 (only 0.2%), a large amount of Si elements are evenly distributed on the surface of all LSACs. Among them, LSAC-3 has the highest relative content of Si elements (about 4.8%). It is well known that SiO2 / Si containing groups are often used to enhance the hydrophobicity of materials. Therefore, the LSACs with the highest t5% and q e5% of LSAC-3 was selected for further hydrophobic modification by covalently grafting -CF2- groups, labeled as LSAC-3-CF2. After modification, LSAC-3-CF2 showed no difference from LSAC-3 in terms of crystal structure, degree of graphitization, and thermal stability, indicating that this mild modification maintained the physical structure and thermal stability of the original LSAC-3 ( Figure 10 ).

[0073] In addition, EDS mapping showed that Si (~3.02%) and F (~0.55%) were uniformly distributed in LSAC-3-CF2 ( Figure 2 e and Figure 11 b), confirming that the fluorine-containing functional groups were successfully grafted onto the surface of LSAC-3. The hydrophobicity of LSAC-3 and the modified LSAC-3-CF2 was further verified by water contact angle (WCA) and water vapor adsorption (WVA) isotherms at 298K. Figure 2 As shown in Figures c and 2f, the unmodified LSAC-3 has a certain hydrophobicity due to its rich SiO2, with a water contact angle of 76.8°. With the attachment of fluorinated functional groups, LSAC-3-CF2 exhibits superhydrophobic properties, with a water contact angle of 153.7°. In addition, the WVA isotherm shows that the water adsorption capacity of LSAC-3-CF2 is only 72.94 mg / g, which is much lower than that of the unmodified LSAC-3 (274.88 mg / g) ( Figure 12 These observations suggest that the strategy of covalently grafting fluorinated functional groups via a [2+1] cycloaddition reaction can effectively enhance the hydrophobic properties of the LSAC-3 surface.

[0074] As mentioned above, an effective hydrophobic modification strategy should not damage or change the pore structure of the adsorbent. Therefore, we compared the pore structure parameters and pore size distribution (PSD) between LSAC-3-CF2 and LSAC-3. Figure 3 As shown in (ab) and Table 1, the modified LSAC-3-CF2 retains most of the pore structure of LSAC-3. The specific surface area (S BET ) and micropore specific surface area (S micro ) are 2411m 2 / g and 2137m 2 / g, and LSAC-3 (2535m 2 / g and 2342m 2 / g), only slightly decreased by about 4.9% and 8.8% respectively, while maintaining a microporosity of about 88.6%, which is a higher micropore ratio than other adsorbents (Table 2).

[0075] In addition, XPS and FTIR analysis were performed to investigate the changes in surface elements and functional groups before and after fluorination. XPS results showed that, unlike LSAC-3, the surface of LSAC-3-CF2 exhibited a characteristic binding energy of F in addition to C, O, and Si elements ( Figure 3 c and Table 5), which is consistent with the EDS results. High-resolution C1s spectrum ( Figure 3 d) was decomposed into four characteristic peaks at 284.8eV, 285.9eV, 286.8eV and 288.8eV, corresponding to CC, CO, C=O and O=CO, respectively. A unique and weak C-F2 peak was observed at 289.9eV for LSAC-3-CF2. The presence of the -CF2- group was verified by high-resolution F1s spectroscopy, with a C-F2 peak at 689.0eV (76.34%) and a CF peak at 686.0eV (23.66%) ( Figure 3 e and Table 5). The appearance of a small amount of CF peaks may be attributed to the influence of alternative reaction pathways during the cycloaddition reaction, resulting in monofluorinated -CF- bonds instead of difluorinated -CF2- bonds. In addition, FTIR spectroscopy further confirmed that the -CF2- groups were successfully grafted onto the LSAC-3-CF2 surface ( Figure 3 f). The difference spectra between LSAC-3 and LSAC-3-CF2 were processed by OMNIC software, and two new characteristic peaks were found, appearing at 1148 cm -1 and 1215cm -1 , corresponding to the stretching vibration of the C-F bond, respectively. In addition, high-resolution Si 2p and O1s spectra reaffirmed the significant presence of SiO2 in LSAC-3 and LSAC-3-CF2 ( Figure 3 (gh) and Table 5). Therefore, it is concluded that the excellent hydrophobicity of LSAC-3-CF2 is attributed to two main factors: (1) the intrinsic hydrophobicity imparted by the abundant SiO2 in the original LSAC-3, and (2) the significantly enhanced hydrophobic property by the covalently grafted -CF2- groups.

[0076] In order to study the effect of -CF2- groups on the dynamic adsorption performance of the adsorbent, the breakthrough curves of LSAC-3 and LSAC-3-CF2 for trace (1 ppm) toluene were tested under different humidity conditions (0%, 50%, 80%, 90% RH). The experimental temperature was 298K ( Figure 5 (ab)). The Yoon-Nelson (YN) and Thomas models were further used to analyze the effect of water vapor on the breakthrough curve of toluene ( Figure 14 The dynamic adsorption performance of toluene under different humidity conditions and the corresponding model fitting parameters are summarized in Tables 6 and 7. Figure 14As shown in Table 7, both Yoon-Nelson (YN) and Thomas models can effectively describe the effect of water vapor on toluene adsorption performance (R 2 ≥0.958). With the increase of humidity, the adsorption rate constant K YN and K T The increase indicates that water vapor can promote the diffusion rate of toluene to a certain extent. Under the condition of 1 ppm toluene in dry air, the 10% breakthrough time (t10%) of LSAC-3 is 2832 min, and the 90% breakthrough capacity (q e 90%) is 156.4 mg / g, which is slightly higher than LSAC-3-CF2 (2520 min and 147.8 mg / g). This may be attributed to the S BET and S micro The reduction (Table 1 and Figure 4 a), thereby reducing the number of effective adsorption sites.

[0077] However, the adsorption performance of LSAC-3-CF2 under humidity conditions was significantly better than that of LSAC-3 (Table 6). As the humidity increased, the t10% and q e 90% showed a downward trend ( Figure 5 c and Figure 13 Specifically, under 50% RH conditions, LSAC-3 exhibited excellent trace toluene adsorption performance due to its high SiO2 content, with t10% and q e Under the same conditions, the t10% and q of the modified LSAC-3-CF2 were 1480min and 92.2mg / g respectively. e The t10% and q90% of LSAC-3 at 50% RH were 2080 min and 145.9 mg / g, respectively, both of which were significantly higher than those reported for other types of adsorbents under similar conditions (Table 6). e90% were reduced by approximately 47.7% and 41.0%, respectively. In contrast, the reduction of the modified LSAC-3-CF2 was only 17.5% and 1.3%. Since LSAC-3 and LSAC-3-CF2 have similar pore structures, the performance difference between them mainly depends on the functional groups on the adsorbent surface. Generally, there are two main ways for water molecules to interact with adsorbents: (1) forming hydrogen bonds with hydrophilic oxygen-containing functional groups (such as hydroxyl and carboxyl groups) on the adsorbent surface; (2) forming hydrogen bonds with other water molecules that have been adsorbed on the adsorbent surface. According to the XPS results, there is almost no difference in the oxygen content of LSAC-3 and LSAC-3-CF2 (Table 5). Therefore, the -CF2- groups covalently grafted on the surface of LSAC-3-CF2 significantly enhanced the adsorption performance of toluene under humidity conditions. On the one hand, the -CF2- groups are non-polar, which is conducive to the adsorption of non-polar toluene molecules. On the other hand, these groups weaken the hydrogen bonding between the adsorbent surface and water molecules, effectively preventing water molecules from penetrating into the internal pore structure of the adsorbent and reducing the possibility of competing with toluene molecules for adsorption sites.

[0078] In addition, at 80% RH, the t10% and q e When the relative humidity increases to 90%RH, the toluene adsorption performance of LSAC-3-CF2 decreases significantly, and the t10% and q e 90% decreased to 304 min and 11.9 mg / g, respectively. This decrease can be attributed to the increased competition between water and toluene molecules under high humidity conditions. Excessive humidity also causes water molecules to fill the adsorbent surface and pore structure, significantly reducing adsorption performance. In summary, dynamic adsorption results indicate that the grafted -CF2- groups significantly enhance the adsorption performance of LSAC-3 for trace toluene under high humidity conditions. These findings further emphasize the critical role of functional group design in improving adsorbent performance in complex environments.

[0079] In order to gain a deeper understanding of the adsorption kinetics of LSAC-3 and LSAC-3-CF2, the PFO and PSO models were used to fit the dynamic breakthrough curves of the two adsorbents under different humidity conditions ( Figure 5 (ef) and Figure S11), and the corresponding kinetic fitting parameters are summarized in Table 8. It is worth noting that compared with the PSO model (R 2 ≤0.748), the PFO model has higher fitting accuracy on the two materials (R 2 ≥0.975). In addition, the saturated adsorption capacity (q e , Cal.) and experimental data (q e, Exp.) are highly consistent, indicating that the adsorption of toluene on the adsorbent is mainly physical adsorption and reversible. In the PFO model, the kinetic constant k1 usually reflects the rate at which the gas phase adsorbate diffuses to the adsorbent surface and interacts with the adsorption sites. With the increase of relative humidity, the k1 of the two materials gradually increases ( Figure 5 d), this phenomenon is consistent with K YN and K T This phenomenon may be attributed to the formation of a thin layer of water molecules on the surface of the adsorbent, which may reduce the diffusion barrier of the adsorbate on the adsorbent surface, provide a smoother path for the migration of toluene molecules, and thus enhance the adsorption rate. Although k1 increases, q e The k1 of LSAC-3 decreased by 90%, indicating that water molecules primarily positively affect the dynamic adsorption behavior by enhancing the diffusion rate, but exhibit a competitive spacer effect on the adsorption capacity. Furthermore, at 50% RH, the k1 difference between LSAC-3 and LSAC-3-CF2 was small. However, at 80% RH, the k1 of LSAC-3 was approximately 2.6 times that of LSAC-3-CF2, further demonstrating the superior anti-wetting properties of LSAC-3-CF2 under high humidity conditions.

[0080] In order to further investigate the thermal regeneration performance of LSAC-3 and LSAC-3-CF2, the dynamic breakthrough curves of the two materials at different temperatures (298K, 318K and 338K) were studied. Figure 6 As shown in the figure, when the temperature increases from 298K to 338K, the t10% of LSAC-3 decreases from 1480min to 268min at 50%RH, and q e 90% decreased from 92.2 mg / g to 26.7 mg / g. At 80% RH, the t10% of LSAC-3-CF2 decreased from 608 min to 104 min, and q e 90% decreased from 46.0 mg / g to 11.8 mg / g. As the temperature increased, t10% and q e The sharp drop of 90% further proves that the interaction between the adsorbent and toluene molecules is mainly physical adsorption. Subsequently, the desorption behavior of LSAC-3 and LSAC-3-CF2 after saturated adsorption at different temperatures was studied ( Figure 15 ). Obviously, the desorption peak of LSAC-3-CF2 appears at 373K, which is 20K lower than that of LSAC-3 (393K). In addition, the complete desorption temperature of LSAC-3-CF2 (423K) is significantly lower than that of LSAC-3. Therefore, 393K and 373K were selected as the regeneration temperatures of LSAC-3 and LSAC-3-CF2, respectively. Figure 6(cd) After two regeneration cycles, both materials still maintained good toluene adsorption performance. Overall, the modified LSAC-3-CF2 exhibited better regeneration ability at low temperatures, significantly reducing the energy consumption and cost of the regeneration process while making the regeneration process safer.

[0081] Table 1 Pore structure characteristics of LSAC and hydrophobically modified LSAC-3-CF2

[0082]

[0083] a Specific surface area obtained with microporous BET additives.

[0084] b Micropore surface area and volume obtained by t-plot method.

[0085] c Mesopore surface area and volume obtained by BJH method.

[0086] d The total pore volume is calculated as P / P0=0.99.

[0087] Table 2 Pore structure parameters of LSAC-3 before and after hydrophobic modification compared with other adsorbents

[0088]

[0089] Table 3 XRF results of LSAC-3

[0090] MgO <![CDATA[Al2O3]]> <![CDATA[SiO2]]> <![CDATA[SO3]]> <![CDATA[Fe2O3]]> 0.059wt% 1.415wt% 96.50wt% 1.271wt% 0.106wt%

[0091] Table 4 D-band and G-band peaks of LSAC and LSAC-3-CF2

[0092] Samples <![CDATA[Dband(1344cm -1 )]]> <![CDATA[Gband(1590cm -1 )]]> LSAC-1 3688 3653 LSAC-2 1715 1730 LSAC-3 2617 2642 <![CDATA[LSAC-3-CF2]]> 2096 2086 LSAC-4 4294 4308

[0093] Table 5 Relative contents of C, O, Si, and F elements in LSAC-3 and LSAC-3-CF2 obtained from high-resolution XPS results

[0094]

[0095] Table 6 Dynamic adsorption capacity of LSAC-3, LSAC-3-CF2 and some other adsorbents for low concentration toluene under different humidity conditions at 298K

[0096]

[0097] Table 7 YN and Thomas model parameters of toluene on LSAC-3 and LSAC-3-CF2

[0098]

[0099] Table 8 Fitting parameters of pseudo-first-order and pseudo-second-order kinetic models for trace toluene adsorption by LSAC-3 and LSAC-3-CF2 under different humidity conditions

[0100]

[0101] The above description of the disclosed embodiments is intended to enable one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be readily apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention is not limited to the embodiments shown herein but is intended to conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing an activated carbon adsorbent for adsorbing toluene, characterized in that: The following steps are involved: Step 1, carbonizing lignin, heating to a target temperature at a constant heating rate, and naturally cooling to room temperature to obtain lignin charcoal; Step 2: Mix and grind the lignin charcoal and the activator, and then heat them to the target temperature at a constant heating rate. After naturally cooling to room temperature, take them out, and wash the surface to neutrality with hydrochloric acid solution and deionized water to obtain lignin-based super activated carbon.

2. The method for preparing an activated carbon adsorbent for adsorbing toluene according to claim 1, characterized in that: Before carbonizing the lignin, the lignin is purified. The purification operation is as follows: lignin is mixed with water at a mass ratio of 1:20, stirred, filtered, the filtrate is heated in a water bath, the pH is adjusted with a hydrochloric acid solution, stirred, centrifuged, the supernatant is removed, and the precipitate is dried to obtain purified lignin.

3. The method for preparing an activated carbon adsorbent for adsorbing toluene according to claim 1, characterized in that: The lignin-based super activated carbon is modified. The modification operation is to mix and heat the lignin-based super activated carbon, a fluorocarbon source, an initiator and toluene, and then cool the mixture to obtain the modified lignin-based super activated carbon.

4. The method for preparing an activated carbon adsorbent for adsorbing toluene according to claim 3, characterized in that: The ratio of the lignin-based super activated carbon, the fluorocarbon source, the initiator and toluene is 15 mg:30 mg:3 mg:1 mL.

5. The method for preparing an activated carbon adsorbent for adsorbing toluene according to claim 3, characterized in that: The fluorocarbon source is TMSCF2Br, the initiator is n-Bu4NBr, and heating is performed under a nitrogen atmosphere at a heating temperature of 110°C for a heating time of 2 hours.

6. The method for preparing an activated carbon adsorbent for adsorbing toluene according to claim 1, characterized in that: In step 1, heating is performed under a nitrogen atmosphere, the nitrogen flow rate is 200 mL / min, the constant heating rate is 3° C. / min, the target temperature is 500° C., and the target temperature is maintained for 2 h.

7. The method for preparing an activated carbon adsorbent for adsorbing toluene according to claim 1, characterized in that: The mass ratio of the lignin charcoal to the activator in step 2 is 1:(1-4).

8. The method for preparing an activated carbon adsorbent for adsorbing toluene according to claim 1, characterized in that: In step 2, the activator is KOH, the grinding speed is 500 rpm, the grinding time is 2 min, heating is carried out under a nitrogen atmosphere, the flow rate is 200 mL / min, the constant heating rate is 5°C / min, the target temperature is 850°C, and the target temperature is maintained for 1 h.

9. Lignin-based super activated carbon prepared by the method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Preparation method and application of three-dimensional lignin-based hierarchical pore activated carbon material

    CN105817202A

  • Modified activated carbon and preparation method thereof, and supercapacitor

    CN113307266A

  • Magnetic activated carbon as well as preparation method, regeneration method and application thereof

    CN113332955A

  • Lignin-based high-specific-surface-area nitrogen-doped porous carbon material as well as preparation method and application thereof

    CN114408917A

Cited By

  • MOF-based gas adsorbent with core-shell-shell structure as well as preparation method and application of MOF-based gas adsorbent

    CN121155535A

  • A core-shell MOF-based gas adsorbent, its preparation method and application

    CN121155535B